Pemasaran Kopi Arabika Di Desa Colol, Kecamatan Poco Ranaka Timur Kabupaten Manggarai Timur - Maria Fatima Deos; Alfetri N. P. Lango; Doppy Roy Nendissa (Undana Press, 2019)
Arabica coffee is one of the important commodity at Mangarai Timur, with the highest area and production among the districts in NTT (BPS NTT 2015), aspects of coffee marketing is a concern for the system Fair marketing in profit sharing .The research aims at know the marketing channels, know the functions - marketing functions, know the marketing margin, farmer's share and the benefits of marketing of Arabica coffee. This research has been implemented in Colol Village by using the survey method by taking samples of 83 arabica coffee farmers and 11 merchants in each marketing agency. Using Random Sampling and Snowball sampling data analysis using margin marketing calculations, farmer's share, and margins between marketing institutes as well as descriptive analysis. The results of this research show that there are 4 channels; First farmer→Gatherer → retailer → IIT (Inter Island Traders); Second channel of farmer → UPH ASNIKOM (Result management Unit of Kopi asoisation Manggarai); Third channel farmer → retailer, and channel into four farmers → IIT (Inter Island Traders. The marketing functions are still relatively limited by marketing institutions that are limited to the function of exchange and transport while the facility functions very minimal. This impacts the margins and profits between the marketing agencies. The largest marketing margin obtained on the first and fourth channel is Rp.38500.00 with Farmer's Share of 53.89% this figure is classed as efficient because > 40%.The benefits are held between the adjustment agencies namely farmers Rp.44.107 , 15/Kg and for the R/C Ratio the largest channel of the fourth 49.00 means that each additional cost of Rp . 1000 will be obtained the acceptance of Rp.49000. Therefore the marketing activities for Arabica coffee on every fourth channel are economicall profitable . Kopi Arabika merupakan salah satu komoditi andalan di Mangarai Timur, dengan luas lahan dan produksi tertinggi diantara Kabupaten yang ada di Nusa Tenggra Timur. Penelitian ini bertujuan untuk, mengetahui saluran pemasaran, mengetahui fungsi – fungsi pemasaran , mengetahui margin pemasaran, farmer’s share dan keuntungan pemasaran kopi arabika. penelitian ini telah dilaksanakan di desa Colol dengan menggunakan metode survei dengan mengambil sampel 83 petani kopi arabika dan 11 pedagang di setiap lembaga pemasaran. menggunakan Random Sampling dan Snowball sampling Analisis data menggunakan perhitungan margin pemasaran, Farmer’s share, dan margin antar lembaga pemasaran serta analisis deskriptif.Hasil penlitian ini menunjukkan bahwa terdapat 4 saluran ; pertama petani →.pengumpul → pengecer → PAP (Pedagang Antar Pulau); saluran kedua Petani → UPH ASNIKOM (Unit Pengelola Hasil Asoisasi Kopi Manggarai); saluran ketiga Petani → pengecer, dan saluran ke empat petani →PAP. Fungsi-fungsi pemasaran masih relatif terbatas dilakukan oleh lembaga pemasaran yaitu terbatas pada fungsi pertukaran dan pengangkutan sedangkan fungsi fasilitas sangat minim dilakukan. Hal ini berdampak pada marjin dan keuntungan antara lembaga pemasaran. Marjin pemasaran terbesar diperoleh pada saluran pertama dan keempat yaitu Rp. 38500,00 dengan Farmer’s Share sebesar 53,89% angka ini digolongkan efisien karena > 40%. Keuntungan dipeoleh antar lembaga pemarasan yaitu petani Rp. 44.107,15/Kg dan untuk R/C Ratio yang terbesar saluran keempat 49,00 artinya setiap penambahan biaya Rp.1000 akan diperoleh penerimaan sebesar Rp. 49.000. Oleh karena itu, kegiatan pemasaran untuk kopi arabika pada setiap saluran keempat secara ekonomi menguntungkan.